The GEO-SPATIAL ASSESSMENT OF THE INFLUENCE OF TEMPERATURE AND RAINFALL ON THE OCCURRENCE OF CHOLERA IN KANO STATE, NIGERIA - Abdullahi, Ahmad Hamza; Hassan, Muhammad Buba; Kanoma, Muhammad S.; Yahuza, Yunusa (FUDMA JOURNAL OF SCIENCES, 2023)
Temperature and rainfall variability as an important factor that could affect the occurrence of Cholera becomes one of the major concerns globally. This study assessed the influence of these factors on the occurrence of Cholera in Kano State, Nigeria. The researchers employed the used of Cholera surveillance data obtained from Kano State Ministry of Health, the mean monthly temperature, and total monthly rainfall data downloaded from the climatic research unit of the University of East Anglia archive (2010 to 2019). The data were analyzed using Ordinary Least Squares (OLS) regression and Geographically Weighted Regression (GWR) in ArcMap 10.8 environment. Results showed that an increase in temperature by 1 unit positively influences the occurrence of Cholera by 19.69, 11.7 and 18.7 unit during hot/dry, warm/wet, and cold/dry season respectively. Similarly, an increase in rainfall by 1 unit brings about a rise in the outbreak of Cholera by 0.67 and 0.97 unit during hot/dry and warm/wet season respectively. In addition, highest influence of temperature and rainfall on the outbreak of Cholera during warm/wet season with R2 value of 0.25, and lowest during the cold/dry season with R2 value at 0.06. Northern part of the State experienced the strongest influence (R2 values of 0.2) while Southern part recorded the lowest influence with R2 values of 0.04 to 0.07. Variability in temperature and rainfall in Kano State were directly related with the outbreak of Cholera. Hence, the need for more environmental sanitation programs and public campaign as climate related mitigation and adaptation strategies.
Keywords: Temperature; Rainfall; Cholera; Geo-spatial; Kano State